2017
DOI: 10.1371/journal.pone.0189318
|View full text |Cite|
|
Sign up to set email alerts
|

Anatomical relationships between serotonin 5-HT2A and dopamine D2 receptors in living human brain

Abstract: Serotonin 2A (5-HT2A) receptors and dopamine D2 receptors are intimately related to the physiology and pathophysiology of neuropsychiatric disorders. A large number of studies have reported the effectiveness of psychotropic agents targeting 5-HT2A and D2 receptors in these disorders. In addition to the individual functions of these receptors, the interaction between the two neurotransmitter systems has been studied in the living brain. However, little is known about their regional relationship in individual hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…These results support the hypothesis of dopamine being a major modulator in the generation of LDAEP and dopamine-serotonin interaction. Clearly, several findings have shown that serotoninergic deficiency is associated with a lack of dopamine [ 62 - 64 ]. A molecular genetic study showed that there are several dopaminergic and serotonergic genes related to reward functioning in ADHD [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results support the hypothesis of dopamine being a major modulator in the generation of LDAEP and dopamine-serotonin interaction. Clearly, several findings have shown that serotoninergic deficiency is associated with a lack of dopamine [ 62 - 64 ]. A molecular genetic study showed that there are several dopaminergic and serotonergic genes related to reward functioning in ADHD [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 5HT2A receptor, encoded by the HT2RA gene, is a robust functional candidate gene in autism [40][41][42][43] , and lower cortical 5HT2A receptor binding has been reported to correlate with social communication differences in autism 44 . The 5HT2A receptor is expressed throughout the cortex but especially in regions related to sensorimotor integration 45 and the so-called default mode network responsible for "self" and "other" processing 46 . At the circuit level, 5HT2A receptor signalling is thought to enhance neural plasticity 47 and increases cortical glutamate and thalamic GABA levels 38 .…”
Section: Targeting the Serotonin System In Autism Using Psilocybinmentioning
confidence: 99%
“…During the scans, arterial blood samples were obtained manually 33 times after radioligand injection to obtain arterial input function (Ishii et al, 2017). Each blood sample was centrifuged to obtain plasma and blood cell fractions, and the concentrations of radioactivity in whole blood and plasma were measured (Ishii et al, 2017).…”
Section: Pet Acquisition and Analysismentioning
confidence: 99%
“…During the scans, arterial blood samples were obtained manually 33 times after radioligand injection to obtain arterial input function (Ishii et al, 2017). Each blood sample was centrifuged to obtain plasma and blood cell fractions, and the concentrations of radioactivity in whole blood and plasma were measured (Ishii et al, 2017). The fractions of the parent compound and its radiometabolites in plasma were determined using high-performance liquid chromatography from 6 samples of each subject (Ishii et al, 2017).…”
Section: Pet Acquisition and Analysismentioning
confidence: 99%